Prospective Randomized Study Comparing Combined Phaco-ExPress and Phacotrabeculectomy in Open Angle Glaucoma Treatment: 12-Month Follow-Up - Joanna Konopińska; Marta Deniziak; Emil Saeed; Agnieszka Bartczak; Renata Zalewska; Zofia Mariak; Marek Rękas (Journal of Ophthalmology)
Purpose of the Study. To compare the efficacy and safety of phacotrabeculectomy (P-Trab) and phacoemulsification with the ExPress (P-ExPress) mini glaucoma shunt implantation. Study Plan. Prospective randomized study. Material and Methods. 85 eyes with cataract and unregulated open angle glaucoma. There were 46 eyes in the P-ExPress and 39 the P-Trab group. Intraocular pressure (IOP), the number of antiglaucoma medications, qualified and complete surgical success (defined as IOP ≤ 18.0 mmHg), visual acuity (CDVA), the number of endothelial cells, and postoperative complications and additional procedures were assessed. Results. After 12 months of observation, the average IOP in the P-Express group went from 26.4 ± 9.3 down to 17.1 ± 5 mmHg (P<0.05) and from 27.9 ± 12.9 down to 15.9 ± 2.7 mmHg in the P-Trab group (P<0.05). No significant differences in the amount of medications used after surgery and CDVA were discovered between the groups. In the P-ExPress group, greater loss of endothelial cells was noted (CDloss%), compared to the P-Trab group. Conclusions. Both P-ExPress and P-Trab have comparable efficacy and similar early postoperative complication profile. The presence of additional implant (as is the case of the ExPress mini glaucoma shunt implantation) may cause progressive loss of endothelial cells.